Application Distal Leg Massage in Diabetes Mellitus Patient Post Lumbar Surgery with Peripheral Arterial Disease: Case Report - Natamia Kyrieleison Habeahan; H. Kosim; Atlastieka Praptiwi (Indonesian Journal of Global Health Research, 2026)
Postoperative lumbar surgery patients with diabetes mellitus are at risk of developing complex neurovascular disorders. Neurological deficits caused by lumbar nerve compression or diabetic neuropathy often result in numbness and tingling in the distal limbs, while impaired peripheral circulation related to diabetes mellitus can delay tissue healing. Distal limb massage is a non-pharmacological intervention that may help improve blood circulation and support peripheral nerve function recovery. To determine the effect of distal limb massage on improving peripheral circulation in post-lumbar surgery patients with diabetes mellitus and peripheral arterial disease (PAD). This descriptive case report with a nursing care approach was conducted from September 13 to 16, 2025, in Room UBK 2 of Welas Asih Hospital. A 46-year-old woman with a lumbar abscess and diabetes mellitus received distal limb massage twice daily for three days (30 minutes/session). Peripheral circulation was assessed using Ankle-Brachial Index (ABI) and plantar temperature before and after intervention and analyzed descriptively. After the intervention, the Ankle-Brachial Index (ABI) increased in the right leg from 1.04 to 1.08 and in the left leg from 0.75 to 0.82. In addition, the average plantar temperature increased by 0.3–0.5°C, indicating improved peripheral perfusion. Distal limb massage demonstrated potential effectiveness in improving peripheral circulation, as reflected by increased ABI values and plantar temperature, and may help reduce numbness and tingling in post-lumbar surgery patients with diabetes mellitus and PAD.